The effect of phosphorus and nitrogen co-doped on the synthesis of diamond at high pressure and high temperature. (January 2016) - Yan, Bingmin; Jia, Xiaopeng; Fang, Chao; Chen, Ning; Li, Yadong; Sun, Shishuai; Ma, Hong-An
Abstract: The synthesis of phosphorus and nitrogen co-doped diamond is investigated in the NiMnCo–C system by adding P3 N5 or carbonyl iron powders mixed with phosphorus powders under high pressure and high temperature. Experimental results show that the color distribution in diamond crystals with low concentration of P3 N5 additive is not uniform. The color becomes deep green with the increase of P3 N5 additive. The optical images and FTIR spectra reveal that the nitrogen atoms are more easily incorporated via 111 than 100 in the same conditions. In addition, the result of FTIR spectra of synthesized diamond indicates that the hydrogen atoms in the form of sp 3 –CH2 – are more likely to enter the diamond lattice in the P/N co-doped system, compared with the single N-doped system. The absorption peak at 3107 cm − 1 attributed to vibration of H-related point defects (sp 2 –CHCH–) is observed in diamonds, which is often found in natural diamonds. The Raman shifting to lower frequency and FWHM value becoming wider are due to the doping of phosphorus atoms. Highlights: The effect of P/N co-doped on the synthesis of diamond under HPHT was investigated. The hydrogen atoms are more easily incorporated into diamond lattice in the P/N co-doped system. The IR absorption peak at 3107 cm − 1 (which often can be found in natural diamond) was observed in the synthesized diamond.